Evaluation of carbon dioxide emissions by Kansas agribusiness retailers - Canales Medina, Dominga Elizabeth (Kansas State University, 2012)
Greenhouse gas (GHG) emissions and their negative effect on the environment is a growing concern in the world. It is estimated that agriculture is responsible for 7% of the total GHG emissions in the United States. Currently, environmental policies to regulate GHG are in place in different countries and are expected to increase in the future. Increased awareness about climate change by customers also represents an incentive for companies in measuring their emissions. The objective of this study is to estimate carbon dioxide-equivalent emissions from eight agribusiness retailers in Kansas. Data consisted of two years of energy inputs from the operation of the agribusiness retailers. Carbon emission coefficients were employed to determine carbon dioxide-equivalent emissions associated with the use of each energy input during their operations. Results suggest that electricity is the largest source of total carbon dioxide emissions from the retail operations followed by diesel fuel. Diesel fuel represents the main source of direct emissions and gasoline represents the second largest source of direct emissions. Emissions from the agricultural sector will not be regulated under the current American Clean Energy and Security Act of 2009 but information on their potential carbon footprint may be used in identifying specific processes where emissions could be reduced and to analyze possible climate legislation implications for their operations. If agribusinesses were to be regulated, none of the eight retailers have locations with emission levels that would be subject to the current cap and trade bill passed by the U.S. House of Representatives. But, if they were regulated and had to comply by purchasing carbon credits equal to 5 to 20% of their direct emissions, the cost would be low given estimation of future carbon prices in the literature. Even if agricultural retailers are not directly restricted, they will likely be affected by increases in energy input prices if such legislation is enacted.
Keywords: Agribusiness; Climate change; Environmental economics; Economics, Agricultural (0503); Environmental economics (0438)